Design And Implementation Of Pose Recording System With Denavit Hartenberg Method In A 6-Dof Robot Rotaric - Susanto, Calvin; Limanuel, Fransisko; Rippun, Ferry (Widya Teknik, 2023)
Robot developments have been integrated into several industrial and home appliances. To keep up with the development, UNIKA Atma Jaya created a group called PATRIOT as a head start, and started the development on ROTARIC robot. One of the early robot research discussed in this paper is to design and implement ROTARIC 6-DOF robot pose recording system which is drawn using forward kinematics with Denavit Hartenberg method. The system has a GUI with several function inside such as robot pose recording, 2-D display of the robot recorded pose using Forward Kinematics analysis, and playback recorded pose. The system uses several hardware that have been connected serially such as 6 Dynamixel MX-28 servo, OpenCM 9.04 +485 EXP microcontroller, and a Computer. The Software used in the system is C# .NET with WinForms App as the GUI and Arduino IDE. From the test done in this research, the recording and 2-D drawing system achieved error <±1cm or 6.67% relative error caused by the resolution value while reading the servo position sensor and the value rounding inside the program. Meanwhile, the playback recording function that uses queue system achieved error of <±1cm and error of ±5cm or 33.3% relative error when the recorded pose is played using real time delay used in recording. The error is caused by the robot failure to keep up with the speed of the recorded pose and the limited torque in servo number 2 in the robot.